KERAGAMAN GENETIK INDUK UDANG WINDU DI PERAIRAN SELATAN PANGANDARAN DAN BINUANGEUN, JAWABARAT - Aliah, Ratu Siti (BPPT)
An evaluation of the Black Tiger Brood Stock (Penaeus monodon) genetic diversity of Pangandaran and Binuangeun was conducted by using the mtDNA diversity of two gene locus of CO I and 12S rRNA to understand their population genetic diversity. The result show that the brood stock of Pangandaran has 17 haplotipe, while from Binuangeun has 13 haplotipe. The result indicated that the genetic diversity of the Balck Tiger brood stock of Pangandaran was higher than thatBinuangeun.Key words : Genetic diversity, Black Tiger brood stock, Pangandaran, Binuangeun